2022
DOI: 10.1002/ajoc.202200335
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐induced Decarboxylative Alkylations Enabled by Electron Donor‐Acceptor Complex

Abstract: We demonstrated herein a versatile protocol for visible-light-induced decarboxylative alkylations enabled by electron-donor acceptor complex. An array of primary, secondary, tertiary and amino acid-derived redox-active esters (RAEs) were all amenable substrates to undergo radical decarboxylation to be coupled with a diverse range of nucleophiles, creating diverse C(sp 3 )À C(sp 3 ) and C(sp 3 )À C(sp 2 ) bonds with high efficiency. It is worth noting that Katritzky's salt and Togni's reagent were also suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Delightfully, water and ethanol were both applicable, and ethanol provided a comparative reaction efficiency with DMSO (entries 10, 11). This result broke the limitation of alcohol solvents in the visible light-driven α-C­(sp 3 )–H bond alkylation of glycine derivatives, leaving an infinite space to enhance the reaction sustainability and workup simplicity. The screening of light sources revealed that the changes in light wavelength all led to a decrease in reaction efficiency (entries 15–17).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Delightfully, water and ethanol were both applicable, and ethanol provided a comparative reaction efficiency with DMSO (entries 10, 11). This result broke the limitation of alcohol solvents in the visible light-driven α-C­(sp 3 )–H bond alkylation of glycine derivatives, leaving an infinite space to enhance the reaction sustainability and workup simplicity. The screening of light sources revealed that the changes in light wavelength all led to a decrease in reaction efficiency (entries 15–17).…”
Section: Resultsmentioning
confidence: 97%
“…Possibly because of the reaction suspension’s suitable and effective light absorption in the blue LED emission region (Figures S22 and S23, see the Supporting Information), only β-ketoenamine-linked 2D-COF-4 gave the satisfactory desired product yield (entry 4). Then, several previously documented homogeneous or heterogeneous photocatalysts in visible light-driven α-C­(sp 3 )–H bond alkylation or arylation of glycine derivatives, such as Eosin Y, Ru­(bpy) 3 Cl 2 , and g-C 3 N 4 , were incorporated into the reaction system to evaluate their compatibility (Table S1, entries 1–3, see the Supporting Information). Regrettably, the results revealed that all these catalysts demonstrated relatively diminished catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations